(untitled) (PANGEEA, 2025)
Distribution channels diversification circuit products used in tourist area Apuseni Mountains. The existence of de distribution circuit functional, allowing reliable transfer of tourism products between retailer and consumer tour operator in the Apuseni Mountains success key for easy access as the tourist offer unparalleled beauty of the area.